Rosyjskie powiedzenia weselne: kilka uwag o specyfice funkcjonowania tekstu obrzędowego w nieobrzędowej sytuacji - Крашенинникова, Юлия (Studia Rossica Posnaniensia, 2016)
The article is devoted to the problem of situating and performing ceremonial texts in non-ceremonial situations and is based on material from wedding speeches made in 1986–2006 in the local tradition of the Vilegodsky district in the Arkhangelsk region. An analysis of texts from the ceremonial genre performed in non-ceremonial situations allows the description of some mechanisms by which a folklore work in different speech situations is born, as well as masterly performance and strategies used by grooms in wedding speeches at the collector’s request (in situations “outside the ceremony”). It enables us to speak about text commonality in repeat performances, and also the correlation of collective and individual, traditional and improvisational in ceremonial texts learned and performed in various situations. Comparing the records of wedding speeches divided into different temporary intervals provides an informative and productive discussion of the problem of specifics in folklore memory and the competence of the performer, mechanisms for memorizing, reproducing, and also the peculiarities of texts with a tendency towards improvisation.